Bullying in Schools: An Exploratory Case Study in High Schools - Ismail, Ariyanti Mareta; Saputri, Syara Zohari; Hasanah, Uswatun (Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Bullying of students is a problem that is currently rampant in schools. It can be seen in the mass media and social media, and even television often shows cases of bullying. Bullying is negative behavior carried out by students to hurt other people. Bullying cases can occur anytime and anywhere. Therefore, schools, especially teachers, must be more concerned about cases of bullying because the impact of bullying will affect students physically and psychologically. This article describes a case of bullying in a senior high school class. The method used was an exploratory study. Researchers explored information and incidents of bullying cases in upper secondary schools, specifically class X.1 in one of the high schools in Banten. Data was collected through in-depth interviews with the homeroom teacher of class X.1, along with the victim and one of the perpetrators of bullying. Based on the results of the interview, it was found that the cause of bullying was a lack of communication between both parties, resulting in misunderstandings between the two parties, egocentrism, emotional feelings, and distrust between peers. Bullying carried out by students consists of verbal, cyber, and social bullying. This bullying is included in moderate bullying because the homeroom teacher can still resolve it by discussing it with all the students. The effort to handle this case is to be a good listener to both the victim and the perpetrator, not compare the two students, and act as a mediator between the two. It is necessary to provide education about bullying so that students know the information and dangers of bullying.